Microvascular caliber changes in intramucosal and submucosally invasive esophageal cancer - Santi, E. G. R.; Inoue, H.; Ikeda, H.; Yoshida, A.; Onimaru, M.; Sato, H.; Maselli, R.; Hayee, B.-H.; Kudo, S.-E. (Endoscopy, 2013)
Background and study aim: Intrapapillary capillary loops (IPCLs) show distinct pattern changes corresponding to tumor progression and depth of invasion, important for in vivo characterization of superficial squamous cell carcinoma (SCC). We examined the relation between invasion depth and histopathologic IPCL diameter. Patients and methods: Prospectively, before lesion resection, magnification endoscopy and narrow band imaging were used to identify IPCL patterns of type V1 (corresponding to tumors limited to the mucosa; 10 patients) and type Vn (submucosally invading tumors; 10 patients). Post-resection, IPCL samples (type I [normal mucosa], n = 103; V1, n = 113; Vn, n = 100) were stained with hematoxylin & eosin, CD34, and desmin, and vessel diameter measured using light microscopy.Results: Mean (standard deviation [SD]) histopathologic calibers of IPCLs of types I, V1, and Vn were significantly different, being 7.7 (2.8) µm, 21.9 (7.4) µm, and 65.2 (22.9) µm; type 1 vs. V1, P < 0.001; V1 vs. Vn, P < 0.001.Conclusions: Magnification endoscopy observation of IPCLs allows in vivo discrimination between intramucosal and submucosally invasive cancer.